1999
DOI: 10.1590/s1516-89131999000200001
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic and teratological effects of mancozeb pre natal exposure on rats

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…In addition, Castro et al confirmed the absence of menstrual cycle alteration in Wister rats exposed to mancozeb concentrations. At the same time, mancozeb do not influence the number of live pup births [37].…”
Section: In Vivo Experimental Studiesmentioning
confidence: 90%
See 1 more Smart Citation
“…In addition, Castro et al confirmed the absence of menstrual cycle alteration in Wister rats exposed to mancozeb concentrations. At the same time, mancozeb do not influence the number of live pup births [37].…”
Section: In Vivo Experimental Studiesmentioning
confidence: 90%
“…To this aim, Cuomo et al suggested that ethylene thiourea exposure in mouse models leads to a remarkable dysregulation of ovarian aging biomarkers, affecting ovarian health [46]. Environmental exposure to ETU, in fact, induces alterations in the estrous cycle, considered the beginning of an early reproductive senescence [37,39,40,46,50]. In addition, Atmaca et al found that mancozeb induces a progressive decline in steroid synthesis in bovine luteal cells [35].…”
Section: Discussionmentioning
confidence: 99%
“…In general, the number of evidences confirming the negative link between the mancozeb and the reproductive system is increasing [1]. Further, the teratogenic impact of mancozeb was reported by considering the ability of mancozeb to cross the rat placental barrier following the administration of 2-3 g/kg mancozeb in Castro's work and 50-500 mg/kg in Rossi's work [17, 34]. Furthermore, a significant decrease in Johnsen's score and spermatogenic cells of first-generation pups in mancozeb-treated group could lead to infertility or a considerable decrease in fertility.…”
Section: Discussionmentioning
confidence: 99%
“…Initially, the use of these chemicals appeared to be lawlessly and effective until excessive and indiscriminate usage became rampant consequently creating problems for human health and the natural atmosphere. Some researchers recorded teratogenicity, residual toxicity, carcinogenicity, prolonged degradation period, ecological pollution, exorbitant cost, and development of resistance among target pests to be associated with some of the commonly used chemicals [10,11]. 10 reported health risks related to ethyl chlorpyrifos, methylchlorpyrifos, and omethoate residues in tomato fruits.…”
Section: E Physicalmentioning
confidence: 99%